DEPOSITIONAL FACIES AND RADIOCARBON AGES FROM DTl CORE IN THE MEKONG RIVER DELTA: EVIDENCE OF INCISED- VALLEY FILLING IN HOLOCENE TRANSGRESSION - Lap, Nguyen Van; Oanh, Ta Thi Kim (Vietnam Journal of Marine Science and Technology, 2008)
The DTJ boring site located in Dong Thap province, 51.5m in depth, gives a good opportunity to study Holocene depositional facies related to sea- level changes at an incised valley of the Mekong River. Based on lithological units and radiocarbon dating, six depositional facies are recognized in asending order as follows: marsh/tidal flat sandy silt, sub- to intertidal flat sandy silt, inner bay/prodelta mud, delta ji-ont sandy silt, sub- to intertidal flat sandy silt and flood plain silty clay facies. A 34. 5m thick- succession from marsh/tidal flat sandy silt facies to inner bay/prodelta mudfacies suggests sea- level rising Moreover, this succession was dated 11,285 to 7, 090 ca.y.BP, and its accumulation rates are high at 4.80- 1 6.20mmy l These data suggest that a high sediment supply from the Mekong River accumulated at the incised valley throughout early to middle Holocene transgression.